If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 11 = 12x + 3 Reorder the terms: 11 + 13x = 12x + 3 Reorder the terms: 11 + 13x = 3 + 12x Solving 11 + 13x = 3 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 11 + 13x + -12x = 3 + 12x + -12x Combine like terms: 13x + -12x = 1x 11 + 1x = 3 + 12x + -12x Combine like terms: 12x + -12x = 0 11 + 1x = 3 + 0 11 + 1x = 3 Add '-11' to each side of the equation. 11 + -11 + 1x = 3 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 3 + -11 1x = 3 + -11 Combine like terms: 3 + -11 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| 2(4x+7)+6x=5(x+10) | | -20+n=3.50 | | (6d+5)-(23d)= | | 5/4-1/3x1/2 | | 11=2x-11 | | -34+2x-7x=76 | | -5x+12=-12x+-12 | | 9-1/3a=-4 | | .25n=-12 | | 2x-9+x+3=-27 | | 4x-3=2(X+13) | | 2x-9+n+3=-27 | | -5x+12=-5x+-12 | | 16Y-7y=500 | | 4x-3+0=-3x-4 | | ((12k^2h)-(3kh^2))/3kh | | 0.25(8-4p)+2p=12 | | 2x+19y=300 | | 60=x+71 | | -3(6-8n)=-138 | | 35-6x=13+5x | | 5(x-2)-8x=-16 | | 8-15=3/7b | | (x)(30-2x)(16-2x)=0 | | 3/5y= | | -16(2.5)+13= | | 23=8n-5+6+3n | | 1/5-8/15 | | a+6(3a+4)=119 | | -5/7*8 | | 8(x-9)-5(x-9)=27 | | 3xy-4z=2x+10 |